KONSEP ISLAMISASI SAINS - muhammad luqman hakim (STAI Al-Hidayat Lasem, 2026)
The Islamization of science is a long-standing process that has taken place since the early emergence of Islam, with the aim of harmonizing scientific knowledge with Islamic values. This process reached its peak during the Abbasid Dynasty through the translation and adaptation of foreign sciences into the Islamic framework. The term Islamization itself became popular in the 20th century through the thoughts of figures such as Muhammad Iqbal, Syed Hossein Nasr, Syed M. Naquib al-Attas, and Ismail Raji al-Faruqi. The Islamization of knowledge is defined as an effort to reconstruct science in accordance with the principle of tawhid (the oneness of God), and to liberate it from the influence of secularism and cultures that contradict Islamic teachings. Its primary objective is to develop knowledge that is not only methodologically scientific, but also aligned with divine revelation and spiritual values. The conceptual approaches include instrumentalism, justification, sacralization, integration, and the Islamic paradigm. From the Islamic perspective, science is not merely a tool for understanding nature, but also part of worship and a moral responsibility of humans in fulfilling their role as stewards (khalifah) on Earth. Therefore, Islam never recognizes a dualism between religious and secular sciences, but rather views both as an integral unity.